Analysis Of Student’s Error In Solving Linear Inequality - Zulhendri; Z. Mawardi Effendi; Darmansyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to describe the analyses of errors that students make in solving Linear Inequality. The method used in this study is a qualitative descriptive method. Questions were given to 3 students of Mathematic program of Pahlawan University. The data collection techniques in this study were the results of students' written tests and the results of interviews related to the results of students' written tests. Based on the results of the research conducted, it is known that the types of student mistakes math in solving the linear inequality problem are: a) Conceptual errors making graphic error solution, error in using the concept of a variable that will be used, identify what is asked and choosing error symbol, and b) Procedural errors include: error in choosing the strategy to be used in problem solving, error in apply strategy to solve the problem and error in viewing return what is the solution obtained is in accordance with what known and asked. Based on the result, the students should be given a meaningful learning to not only memorize the formula but also solve the linear inequality.